Hydrolytic degradation kinetics of bisphenol E cyanate ester resin and composite. (May 2018) - Throckmorton, James A.; Feldman, Greg; Palmese, Giuseppe R.; Guenthner, Andrew J.; Lamison, Kevin R.; Redeker, Neil D.; Ruth, Patrick N.
Abstract: Cyanate ester resin systems offer promise for many high-temperature polymer applications, but the potential for many applications is limited due to hydrolytic degradation of the cured polymer network, which can blister the resin, decrease its cross-linking density, and reduce the maximum allowable use temperature. This study examines the hydrolytic degradation of a Bisphenol E dicyanate ester (LECY) and a glass-fiber composite of LECY. Equilibrium water sorption, reaction rates, and glass transition temperature changes are monitored. Despite differences in diffusion and sorption, the glass fiber composite is shown to behave similarly to the neat polymer system in terms of degradation. Results were compared to PT-30 triphenolic cyanate ester, and LECY was determined to have lower equilibrium water sorption values, and a lower degradation rate. Graphical abstract: